Challenges of community participation in health emergency and disaster risk management in an Iranian context: a qualitative study - Mahmodi, Mohammad Azim; Farrokhi, Mehrdad; Hosseini, Seyyed Mohammad Reza; Najafi, Mehdi; Motlagh, Mohammad Esmaeel; Khankeh, Hamid Reza (Frontiers in Public Health, 2025)
BackgroundDisasters are considered one of the major threats to the health of communities. Given the global spread of disasters, there has been a renewed emphasis in recent years on using community participation approaches in disaster risk management. Community participation in field of emergency and disaster health in Low and Middle-income countries faces a lot of challenges.ObjectiveThe objective of this study is to explore the specific challenges faced by communities in Iran concerning their participation in health emergency and disaster risk management.MethodsIn this study, a qualitative content analysis as research methodology was employed. Purposeful sampling was conducted from June 2023 to May 2024 among community members who were willing to participate and had experience collaborating during disasters. Data were collected through semi-structured in-depth interviews and analyzed using Graneheim and Lundman’s method. The rigor of the study was ensured using Lincoln and Guba’s criteria. Each interview was recorded, transcribed into a word document, and then uploaded into MAXQDA (2020). A total of 23 interviews were conducted with 20 participants.ResultsThere were 15 males and five females participating in the study including healthcare managers, academic people, and laypeople. Data analysis revealed nine distinct categories, which were grouped into three overarching themes based on their similarities. These themes addressed issues of insufficient risk perception, community traumatization, and poor social capital.ConclusionThis study sheds light on the multifaceted challenges that hinder effective community participation in health emergency and disaster risk management in Iran. Addressing these barriers is essential for enhancing community resilience and ensuring effective disaster preparedness. To overcome these challenges, it is imperative for policymakers, healthcare managers, and community leaders to collaborate and implement comprehensive strategies that foster community participation.